Package inserts for prescribed medicines: what minimum information do patients need?. Issue 6145 (21st October 1978) - Hermann, F; Herxheimer, A; Lionel, N D
Abstract : The information a patient needs about a prescribed medicine can be determined by considering what responsibilities he can assume in relation to taking medicine. When the medicine has been dispensed the patient needs to know how to take the drug; how to store the drug; how it is expected to help; and how to recognise problems and what to do about them. A guide was designed to specify what information is required to meet these needs. Using this guide, a set of minimum information on tetracycline was prepared that aimed at being brief, specific, and readable. The best format for the information remains to be determined. Since leaflets produced by professional organisations are generally unsuitable for these purposes, information sets should be put together by small independent groups consisting of clinical pharmacologists, clinicians, pharmacists, and consumers. Each country should produce its own sets, adapting model sets to the circumstances of local practice.